Post-accelerated beams at ISOLDE *This article belongs to the Focus on Exotic Beams at ISOLDE: A Laboratory Portrait special issue. (29th June 2017) - Kadi, Y; Blumenfeld, Y; Delsolaro, W Venturini; Fraser, M A; Huyse, M; Koufidou, A Papageorgiou; Rodriguez, J A; Wenander, F
Abstract: This paper presents an overview of the REX-ISOLDE post-accelerator and a detailed description of the high intensity and energy ISOLDE (HIE-ISOLDE) energy upgrade. The status of the HIE-ISOLDE post-accelerator and its performance, including time structure, beam spot size, beam purity, etc. is presented. The high-energy beam transfer line is also described in detail and an overview of present and future instrumentation and plans for further developments is given. Finally, the hardware and beam commissioning is presented.